Sensation Seeking’s Differential Role in Face-to-Face and Cyberbullying: Taking Perceived Contextual Properties Into Account - Graf, Daniel; Yanagida, Takuya; Spiel, Christiane (Frontiers in Psychology, 2019)
A number of studies have demonstrated a relationship between sensation seeking and aggression. However, few studies have examined the relationships between sensation seeking and traditional and cyberbullying. The few studies that do exist assessed sensation seeking with items partly referring to antisocial behavior. This could have led to tautological findings. Moreover, recently discussed contextual properties that could potentially account for differences between bullying contexts (face-to-face, cyberspace) were neglected. Therefore, the first goal of the present study was to investigate the relationships between sensation seeking and traditional and cyberbullying in a way that avoids tautological findings. Thus, sensation seeking was operationalized as a motivational disposition encompassing the dimensions ‘need for stimulation’ and ‘avoidance of rest’. Furthermore, students’ perceptions of the contextual properties of the face-to-face and cyber context and their relevance for the relationships between the dimensions of sensation seeking and traditional and cyberbullying were examined. A total of 523 students (Mage = 17.93; SD = 2.13; ♀ = 37.4%) from four vocational schools answered online questionnaires on traditional and cyberbullying involvement, perceived contextual properties and the two dimensions of sensation seeking during regular school hours. Structural equation modeling revealed positive associations between need for stimulation and both forms of bullying. Avoidance of rest, however, was positively related to cyberbullying only. The differences in all regression slopes between contexts were statistically significant. That is, the positive associations with the two dimensions of sensation seeking were stronger for cyberbullying than for traditional bullying. Dependent t-tests revealed differences in students’ perceptions of contextual properties between contexts (face-to-face, cyberspace). Nevertheless, no significant relationships between either dimension of sensation seeking and either form of bullying were moderated by any perceived contextual property. Our results demonstrate sensation seeking´s greater role in cyberbullying and confirm differences in perceived contextual properties between the face-to-face and cyber context. Furthermore, the fact that no perceived contextual property moderated the significant relationships between the dimensions of sensation seeking and traditional or cyberbullying shows the relatively greater role of a single person factor compared to single contextual properties.